Efisiensi Asuransi Syariah di Indonesia dengan pendekatan Data Envelopment Analysis - Mustica Bintang Sabiti; Jaenal Effendi; Tanti Novianti (AL-MUZARA'AH, 2017)
The purpose of this study is to estimate the efficiency level of Islamic insurance companies in Indonesia. The data used are taken from each financial report of 14 Islamic life insurance companies and 12 Islamic general insurance in the period 2013-2015. Efficiency score estimation is done by using Data Envelopment Analysis (DEA) method. There are three input variables, namely asset, load, claim payment and two output variables, namely income and tabarru’ funds obtained. The results show that islamic life insurance and islamic general insurance companies in Indonesia have not been operating efficiently.